2016
DOI: 10.3390/ijerph13060539
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Osteomyelitis: An Update on Diagnosis and Treatment

Abstract: Osteomyelitis in children is a serious disease in children requiring early diagnosis and treatment to minimize the risk of sequelae. Therefore, it is of primary importance to recognize the signs and symptoms at the onset and to properly use the available diagnostic tools. It is important to maintain a high index of suspicion and be aware of the evolving epidemiology and of the emergence of antibiotic resistant and aggressive strains requiring careful monitoring and targeted therapy. Hereby we present an instru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 35 publications
2
32
0
7
Order By: Relevance
“…Similarly, in other studies, leukocytosis has been reported only in 36% of children, but increased ESR was observed in 91% of children and CRP in 81% of them [27]. As expected, we observed a low sensitivity of X-ray imaging [28] and US [4]. …”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in other studies, leukocytosis has been reported only in 36% of children, but increased ESR was observed in 91% of children and CRP in 81% of them [27]. As expected, we observed a low sensitivity of X-ray imaging [28] and US [4]. …”
Section: Discussionsupporting
confidence: 89%
“…CT, which is suitable for patients with contraindications to MRI [8], is useful for nding necrotic bones, which assists in the diagnosis of chronic osteomyelitis. MRI has a high sensitivity (82% -100%) and speci city (75% -99%) and is helpful for reaching a diagnosis of osteomyelitis [9]. MRI helps locate lesions, de ne the extent of the destruction, track the development of the disease and plan surgical interventions.…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur beschrieben werden auch Pilze und Viren als seltene Verursacher der Erkrankung [4,5]. In seltenen Fällen und insbesondere bei Kindern liegt eine nicht chronische, nicht bakterielle Erkrankung vor, die als autoinflammatorische Erkrankung dem rheumatischen Formenkreis zuzuordnen ist [6].…”
Section: Definition Des Begriffs Osteomyelitisunclassified